Application of fungicides in integrated disease management of winter wheat in Penza region - Tarakanov Rashit; Chebanenko Svetlana; Dzhalilov Fevzi (BIO Web of Conferences)
Within the framework of the work a field evaluation of the effectiveness of modern fungicides in the protection of winter wheat from major diseases in the conditions of Penza region was carried out. The biological and economic efficiency of fungicides was compared within the framework of complex evaluation. It was found that the double application of fungicides (in the phase of flag leaf and in the phase of earing) significantly reduced the development of leaf diseases (brown leaf rust, septoria leaf spot, powdery mildew) and fusarium head blight. Maximum biological efficiency (up to 93%) and yield increase (up to 12 q/ha) was provided by the use of the scheme with fungicides Abacus Ultra (in the flag leaf phase) and Prozaro (in the flowering phase). Compared to the variant without treatment, grain yield increased from 32 to 44 q/ha, and the profitability of production increased to 19.7%. The obtained results confirm the feasibility of using combined fungicide protection of winter wheat and can be recommended for agricultural practice.